2011
DOI: 10.1371/journal.pone.0021929
|View full text |Cite
|
Sign up to set email alerts
|

Both the C-Terminal Polylysine Region and the Farnesylation of K-RasB Are Important for Its Specific Interaction with Calmodulin

Abstract: BackgroundRas protein, as one of intracellular signal switches, plays various roles in several cell activities such as differentiation and proliferation. There is considerable evidence showing that calmodulin (CaM) binds to K-RasB and dissociates K-RasB from membrane and that the inactivation of CaM is able to induce K-RasB activation. However, the mechanism for the interaction of CaM with K-RasB is not well understood.Methodology/Principal FindingsHere, by applying fluorescence spectroscopy and isothermal tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 51 publications
4
35
1
Order By: Relevance
“…Several studies have examined the selective interaction between K-ras and Ca 2+ /CaM1112 and examined the K-ras-binding state(GTP versus GDP), which we have verified and confirmed (Supplementary Fig. 5b,c).…”
Section: Resultssupporting
confidence: 77%
“…Several studies have examined the selective interaction between K-ras and Ca 2+ /CaM1112 and examined the K-ras-binding state(GTP versus GDP), which we have verified and confirmed (Supplementary Fig. 5b,c).…”
Section: Resultssupporting
confidence: 77%
“…Targeting the allosteric lobe will require assays that detect binding at those sites in high-throughput screens, and the hypotheses derived from structural analysis of specific mutants regarding the activation of the allosteric switch need to be confirmed. Another unexplored area of opportunity is interaction between the C-terminal hypervariable region and switch II in K-RAS4B with calmodulin, which results in signal attenuation (81)(82)(83)(84). Although promotion of protein-protein interaction is not trivial, it is not unprecedented (85) and should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The KRAS4b C-terminus has some propensity to form a helix [49], however, it lacks the hydrophobic anchor residues of the canonical CaM targets. Most, but not all studies have reported that CaM binding to KRAS4b requires farnesylation [43,44,46,[50][51][52][53][54][55], and there are discrepancies in the literature about whether or not the GTPase domain or the nucleotide to which it is bound (GTP versus GDP) plays a role in the interaction.…”
Section: Kras4bmentioning
confidence: 99%
“…There have been a number of studies performed to elucidate the nature of CaM binding to KRAS4b. Not surprisingly, earlier studies focused on probing the direct interaction between CaM and the GTPase-domain of KRAS and proposed this interaction is GTP-dependent [43,45,50,51]. On the other hand, other researchers reported negative evidence for this interaction and concluded that KRAS G-domain does not bind CaM [44,46,51,53,54].…”
Section: Structural Characterization Of Cam Binding To Kras4bmentioning
confidence: 99%
See 1 more Smart Citation